Supporting resilient food systems: Navigating challenges in U.S. rural communities - Brianna Routh; Yoshie Sano; Leah Pylate; Dawn Contreras; Sarah Feeney; Kimberly Greder; Doris Cancel-Tirado; Bradford Wiles (Journal of Agriculture, Food Systems, and Community Development, 2025)
This study examined how food systems in rural communities developed resilience during the COVID-19 pandemic. Using a qualitative research design, we conducted semi-structured interviews with purposive community key informants (CKIs) in rural communities (designated a RUCA code 7 and higher) across 13 U.S. states. CKIs across five sectors (education, food, healthcare, family-service, and Extension) were interviewed, and 38 met the study inclusion criteria of discussing organizational connection to the food system during their interview. Interview questions explored partnerships, supports, challenges, and organizational lessons learned while navigating the COVID-19 pandemic. The research team used a collaborative and iterative approach to coding the interview transcripts. After inductive coding, codes were grouped by similarity and alignment with theory-driven organizational action to identify themes specific to food systems. CKIs shared strategies to address rural food needs that were shaped by factors such as rural community stressor, conditions and characteristics, formal and informal community network structures, social capital, community capacity, and rural food systems resilience. The findings highlight the capacity of rural community organizations to collaborate to enhance food security during a community stressor. It is crucial for rural food systems to integrate these insights and strategies into their practices to effectively prepare for and tackle future challenges.